SYNTHESIS OF NANOHYDROXYAPATITE FROM BUKIT JIMBARAN LIMESTONE - Amerta, Gede Arya; Mardana, Ida Bagus Putu; Yasa, Putu (Indonesian Physical Review, 2026)
The global demand for biocompatible biomimetic materials drives the development of nanohydroxyapatite (HAp) for biomedical applications. This study aims to synthesize nanohydroxyapatite (Ca₁₀(PO₄)₆(OH)₂) from Bukit Jimbaran limestone, Bali, through a precipitation method. XRF analysis shows that the limestone contains 99.62% CaO, which is the main source of calcium. FTIR results detect the presence of phosphate (PO₄³⁻), carbonate (CO₃²⁻), calcium oxide (CaO), and hydroxyl (OH⁻) groups, confirming the formation of the typical HAp structure. The XRD diffraction pattern showed good agreement with JCPDS 09-0432, with major peaks on the (211), (112), and (300) planes, lattice parameters a = b = 9.45 Å and c = 6.85 Å, an average crystallite size of 8.70 nm, and a crystallinity of 92.88%. SEM-EDX analysis revealed agglomerated particle morphology, with a Ca content of 32.0 wt.% and a P content of 14.0 wt.%. The high crystallinity and very small crystallite size confirm the potential of this synthesized HAp to enhance bioactivity and accelerate bone integration, making Jimbaran limestone HP a strong candidate in the biomedical sector.